The dominant role of aerosol-cloud interactions in aerosol-boundary layer feedback: Case studies in three megacities in China - Xiong, Changrui; Li, Jing; Liu, Zhenxin; Zhang, Zhenyu (Frontiers in Environmental Science, 2022)
Aerosols have been found to exacerbate air quality through their interactions with the planetary boundary layer (PBL), but their impacts through the interaction with clouds remain unclear. In this study, we conducted model simulations to evaluate the direct, semi-direct and indirect effects of aerosols in PBL structure and surface PM2.5 concentration during three heavy haze events under overcast conditions. Overall, the aerosol-PBL feedback results in a 22~36% decrease of PBL height and 5~28% increase of PM2.5 concentration. The indirect effect always has the largest impact on PBL and PM2.5 pollution, accounting for 59~84% of the changes. The semi-direct effect is the weakest on average, although it can exceed the direct effect at certain times and locations. Black carbon aerosols play the vital role in both the direct and semi-direct effects. Our findings promote the understanding of heavy haze formation, and highlight the dominant role of aerosol-cloud interaction in the feedback process of aerosols to PBL structure and air quality.